Peak Power Output After 1 Hour Cycling at Variable vs Constant Power in Cyclists and Triathletes. - Etxebarria, N.; Mellor, S.; Ferguson, R. (National Elite Sports Council 2009 Athlete Services Forum - High Performance Programming for Success - 11-12th November - Satellite Program - Applied Physiology Conference 2009 - Australian Institute of Sport, Canberra - 10th, 11th and 13th November, 2009)
The physiology underlying endurance events such as cycling have been well studied. The 40km cycle leg of a triathlon lasts ~1hr and it is of great interest for coaches and sports scientists to know more about how tactics, pacing, drafting and technical courses affect the subsequent running performance of the athletes. Previous work has shown that variable intensity cycling can elicit a different muscle fatigue response to constant load cycling (1,2). However, the previous research has used both low and supra percentages of maximal aerobic power (MAP) in the variable intensity profiling although neither studies resemble the level of exercise intensity and duration observed during a triathlon. Therefore, the aim of this study was to study the decrement in power between a stochastic and steady state 1 hour cycle. Methods 9 male well trained cyclist and triathletes performed a maximal test (¡«10 min) on an SRM cycle ergometer to determine their MAP as the highest average watts for 60 seconds. Participants performed two experimental trials where they cycled a) 1 hour at variable power (i.e. between 45 and 140% MAP) or b) 1 hour at a steady state both averaging ~60% of their MAP determined from the maximal test. Participants then performed a 30sec all out effort before and after each one of the experimental trials. Results The mean peak power output (PPO) for the stochastic and the steady state protocols were very similar (869W and 866W respectively). However, the mean power post- 1 hour cycling was 819W for the stochastic and 863W for the steady state. The mean power for the duration of 30seconds pre- and post- the stochastic trial were 560W and 526W and for 567W and 565W for the steady state trial. There were no substantial differences preand post- measurements between the trials for peak cadence and time to PPO. Discussion/Conclusion Although triathletes might average the same power output for two different races, tactics, the technicality of the course and specific demands of each race affect their performance ability. Training sessions should explicitly target specific racing demands.